PENGARUH KEYAKINAN, PREFERENSI DAN KENDALA TERHADAP NIAT MEMPEROLEH KUALIFIKASI PROFESIONAL PADA MAHASISWA S1 AKUNTANSI UNIVERSITAS STEKOM KENDAL - Nila Diva Safitri; Ratnaningrum Ratnaningrum; Munifah Munifah; Haris Ihsanil Huda (Universitas Boyolali, 2026)
This study aims to examine the influence of beliefs, preferences, and constraints on the intention of undergraduate Accounting students at Stekom Kendal University to obtain professional qualifications. This study is motivated by the increasing need for professionals in the accounting field, which has not been fully followed by high student interest in continuing professional education or obtaining certification. The method used is a quantitative approach with a survey technique through the distribution of questionnaires. Sampling used the Slovin formula with a total of 257 respondents using a purposive sampling technique. Data were analyzed using multiple linear regression techniques to determine the influence of each variable both partially and simultaneously. The results of the study indicate that job prospect beliefs, social beliefs, ability beliefs, and preferences have a positive effect on students' intention to obtain professional qualifications, while the constraint variable has a negative effect. Together, these three variables are thought to have a significant influence on students' intention to obtain professional qualifications. This study is expected to be a consideration for educational institutions in developing programs that support the improvement of students' professional competence, as well as a reference for further research.